Nickel And Danatara Downstreaming: Strategies To Strengthen Food Independence, The Tourism Sector, And The Welfare Of Msmes - Agus Hardaya; Rosalina Andriyani Ebang Pareira; Erlita Khrisinta Dewi; Mohammad Sawir; Hezron Sabar Rotua Tinambunan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a qualitative study with a descriptive approach, namely quality research with a descriptive approach in explaining the main topics in this article. The data used in this study is secondary data that researchers obtained from various credible sources such as books, scientific articles, and so on. The data obtained was analyzed through the stages of data collection, data reduction, data selection, and drawing conclusions. The conclusion in this article show that The Nickel Downstreaming Program has significant potential to improve these three sectors, but this potential comes with trade-offs:1. Food Security: Improved through fiscal strengthening, but threatened by environmental risks. 2. Tourism: Improved through infrastructure and business tourism, but threatened by environmental degradation. 3. MSMEs: Benefit directly from local market demand. To ensure a sustainable positive impact, the government must focus on rigorous environmental risk mitigation and MSME mentoring programs so that economic benefits are not solely enjoyed by large corporations. The establishment of Danantara has significant potential to simultaneously improve Food Security, the Tourism Industry, and the Welfare of MSMEs, through its primary role as a professional and strategic financing institution. Danantara addresses the funding and governance barriers that have hampered the development of these three sectors in Indonesia. Its successful implementation will depend on:1. Transparency and Accountability: Maintaining clean governance so that investment funds are properly targeted. 2. Inclusiveness: Ensuring that large-scale investments not only benefit large corporations but also empower MSMEs and local communities.